Analisis Cemaran Mikrobiologi Pada Daging Ayam Broiler Yang Beredar Di Pasar Tradisional Kecamatan Denpasar Barat - Anak Agung Diah Apriyanti; I Wayan Sudiarta; Ni Made Ayu Suardani Singapurwa (Fakultas Pertanian, Universitas Warmadewa, 2020)
Broiler chicken meat is chicken meat that is commonly consumed by the public, because it has high nutritional value, thicker meat and is easily available in both traditional and modern markets. This study aims to determine the microbiological contamination of broiler chicken meat circulating in the Traditional Market of West Denpasar District. This research is a descriptive study using survey and experimental methods in the laboratory. Based on data from PD Pasar Denpasar City, there are 6 traditional markets in West Denpasar District. The number of samples to be studied was 53 samples from 113 populations. The parameters in this study were Total Plate Count (TPC), Escherichia coli, and Salmonella sp. The results showed that from 53 samples, TPC test results, there were 35 samples that met the requirements and 18 samples exceeded the limits set by SNI 7388: 2009 with a maximum limit of TPC contamination of 1 x 106 colony/gram. E. coli test results, namely 1 sample meets the requirements and 52 samples exceed the limit set by SNI 7388: 2009, namely the maximum limit of E. coli contamination 1 x 101 colony/gram. Salmonella sp. Test results obtained all negative samples so that they meet the requirements of SNI 7388: 2009, namely negative/25 grams.